VULCAN: A "hammer" for high-temperature materials research. (November 2019) - An, Ke; Chen, Yan; Stoica, Alexandru D.
Abstract: Abstract : Understanding changes in chemistry, microstructure, and physical properties during synthesis, processing, testing, and even service is vital for materials design and performance. Compared to traditional postmortem material characterization tools, in situ crystallographic characterization can provide considerable data and information on evolution of chemistry, dislocations, twinning, texture, and strains when a material is under external stimuli. Neutrons especially are able to probe material bulk properties and behaviors in extreme environments, thanks to their deep penetrating power and unique sensitivity to differentiate elements from lightweight to transition-metal atoms. In this article, we introduce and describe a diffractometer named VULCAN, which is located at Oak Ridge National Laboratory. This represents a powerful tool to understand materials properties and behaviors under complex environments, in particular, at high temperatures.